Rapid voltammetric identification and determination of simvastatin at trace levels in pharmaceuticals and biological fluid - Nigović, Biljana; Komorsky-Lovrić, Šebojka; Devčić Stanković, Dubravka (2008)
Abstract: Simvastatin is used as an antilipemic agent through inhibition of 3-hydroxy-3-methylglutarylcoenzyme A reductase. The reduction behavior of drug has been studied in different supporting electrolytes within the pH range 3–9. Based on the adsorptive character of simvastatin onto the mercury electrode surface, a new cathodic square-wave stripping voltammetry method for its direct determination at trace levels has been proposed. The voltammetric response could be used to determine drug concentration in the range 1.0 × 10–8 to 7.5 × 10–7 mol L–1, with detection limit of 4.5 × 10–9 mol L–1. Applicability to biological fluid analysis was illustrated. The method was successfully employed, without sample pretreatment, for quantitation of the active ingredient simvastatin in pharmaceuticals. The use of abrasive stripping voltammetry for rapid identification of this drug in pharmaceutical dosage forms using a paraffin-impregnated graphite electrode has been examined
Bibliografija: 20 jed
Sažetak
Keywords: Antilipemici -- Simvastatin -- Enzimi -- Reduktaza -- Voltametrija -- Abrazivna voltametrija -- Pravokutnovalna voltametrija